Aesthetics word word Allah in Kufic script design configurations: عادل سعدي فاضل السعدي (Al-Academy, 2015)
Taken the word the word God itself the task when the Muslim calligraphers because of its holiness and majesty and altitude, so take Calligraphers innovate in their design, which represents the images and forms experiencing them prolific artistic output to highlight the aesthetic value through the use of Kufic script which is one of the most prominent lines his susceptibility diversity decorative Add the possibility of extending the letters in different directions because of the vision calligrapher aesthetic and an investigation is required for the word of the design, so the researcher examined by dividing into four chapters,Was the first research problem and the importance and goals and identify the term, while the second chapter was divided into two sections was the first diversity formal configurations word Allah in Kufic script, this section on two axes, while the second section Fajss to the aesthetics of the word word Majesty design, and touched the researcher to the most important foundations that have been adopted to achieve Nlk aesthetics, the third chapter devoted to research procedures and analysis of the samples according to the principal researcher in the form set out that his research tool, and the fourth quarter was the findings, conclusions and recommendations and proposals.